The Function of Euphemisms in Communication (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
Euphemisms are linguistic constructs used to substitute socially taboo or sensitive expressions with more socially acceptable or less offensive alternatives. They play a crucial role in communication, allowing individuals to navigate sensitive topics, maintain politeness, and adhere to social norms. This article delves into the sociolinguistic and pragmatic features of euphemisms across various languages, highlighting their significance in interpersonal communication.